A Dynamic Panel Model of Tourism Performance and Income Inequality in Indonesia - Yusrin S Hasan; Roy Anshor; Fathimah Kurniawati; Annisa Pratiwi Katili; Zumran Ibrahim; Refinna Cesari Jacobus; Mega Nurannisa Hippy (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
This study investigates the dual role of tourism performance in shaping income inequality across Indonesia’s 33 provinces from 2014 to 2019. Although the sector’s contribution to the national economy declined during this period, its potential for future growth, particularly through youth-driven innovation, remains significant. Using a dynamic panel GMM approach, we analyze both the short and long-term effects of tourism performance on income inequality, capturing immediate and persistent impacts often overlooked in cross-sectional studies. Our findings reveal that tourism growth exacerbates income inequality in both temporal dimensions, underscoring the need for inclusive policies that engage stakeholders from government and businesses to local communities and youth innovators to ensure tourism becomes a driver of equitable development. As a novel contribution, this study systematically examines the immediate and sustained effects of tourism on wealth distribution while assessing causal relationships between income inequality and key economic indicators, including poverty levels, human development index, population dynamics, and unemployment. These insights advance understanding of the complex interplay between tourism development and socioeconomic disparities in Indonesia.